2022
DOI: 10.1177/0271678x221077339
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of blood-based protein biomarkers reflecting coagulation relates to the burden of cerebral small vessel disease

Abstract: Biological processes underlying cerebral small vessel disease (cSVD) are largely unknown. We hypothesized that identification of clusters of inter-related bood-based biomarkers that are associated with the burden of cSVD provides leads on underlying biological processes. In 494 participants (mean age 67.6 ± 8.7 years; 36% female; 75% cardiovascular diseases; 25% reference participants) we assessed the relation between 92 blood-based biomarkers from the OLINK cardiovascular III panel and cSVD, using cluster-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…In addition, the authors found a mediation effect of the biomarker cluster on the relation between age and WMH ratio (proportion mediated 17%), and hypertension and WMH volume (proportion mediated 21%). Therefore, the authors suggested the involvement of coagulation abnormalities in the etiology of CSVD 135 . In conclusion, these studies suggest that the composite measures of multiple functional‐interrelated biomarkers may be more relevant to CSVD than individual biomarkers.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, the authors found a mediation effect of the biomarker cluster on the relation between age and WMH ratio (proportion mediated 17%), and hypertension and WMH volume (proportion mediated 21%). Therefore, the authors suggested the involvement of coagulation abnormalities in the etiology of CSVD 135 . In conclusion, these studies suggest that the composite measures of multiple functional‐interrelated biomarkers may be more relevant to CSVD than individual biomarkers.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, the authors suggested the involvement of coagulation abnormalities in the etiology of CSVD. 135 In conclusion, these studies suggest that the composite measures of multiple functional-interrelated biomarkers may be more relevant to CSVD than individual biomarkers.…”
Section: Ta B L E 3 Associations Of Hemostasis Factors With Mri Featu...mentioning
confidence: 75%
“…7 Since not all existing proteinprotein interactions are already known, we used both prior knowledge and data-driven cluster analyses based on our Olink V R data to suggest novel protein-protein interactions. This combination of prior knowledge and data-driven cluster analyses also proved effective in previous studies, such as in cerebral small vessel disease, 7 diabetes, 26 heart failure, 27,28 and cancer. 6,29 Of note, the mean differences in CBF between patients and controls were modest and the relationship between lower CBF and MACE was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Typical neuroimaging features of CSVD on magnetic resonance imaging (MRI) include white matter hyperintensity (WMH), lacunes, enlarged perivascular spaces (EPVS), cerebral microbleeds (CMBs), and brain atrophy (BA) 3 . Previous studies have identified a spectrum of traditional vascular risk factors and blood‐based biomarkers for CSVD 4–7 . However, despite abundant literature on this subject, these is insufficient explanation regarding the biological processes of CSVD.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Previous studies have identified a spectrum of traditional vascular risk factors and blood‐based biomarkers for CSVD. 4 , 5 , 6 , 7 However, despite abundant literature on this subject, these is insufficient explanation regarding the biological processes of CSVD. Therefore, identifying novel biomarkers for a better understanding of CSVD may provide a strong foundation for advances in knowledge and clinical management.…”
Section: Introductionmentioning
confidence: 99%